2011
DOI: 10.1186/1475-2891-10-123
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetables intake among elderly Iranians: a theory-based interventional study using the five-a-day program

Abstract: BackgroundThe benefit of FV intake in old age is well documented. However, there is evidence that old people do not consume enough FV. The purpose of this study was to evaluate the effectiveness of a tailored nutrition intervention that aimed to increase the FV intake among elderly Iranians aged 60 and over.MethodsThis quasi-experimental study was performed among a community-based sample of elderly in Tehran, Iran in year 2008 to 2009. Data were collected at baseline and 4 weeks follow-up. At baseline face-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 23 publications
0
38
0
4
Order By: Relevance
“…However, a quasi-experimental study showed that even more improvement in lifestyle (i.e. eating more FV) can be obtained in an elderly population with proper interventions (9). There are not any reports about FV consumption using TTM model regarding stages of change from the developing countries; so, it seems difficult to compare our findings with them.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, a quasi-experimental study showed that even more improvement in lifestyle (i.e. eating more FV) can be obtained in an elderly population with proper interventions (9). There are not any reports about FV consumption using TTM model regarding stages of change from the developing countries; so, it seems difficult to compare our findings with them.…”
Section: Discussionmentioning
confidence: 76%
“…Hence, interventions on changing FV consumption may aim to reduce the importance of negative beliefs arising from behavior change (20). The efficacy of stagetailored nutrition education has been demonstrated in several studies though there were some differences (9,36,37,38). Although some studies have failed to find any significant pros factor for predicting the stages of change (20,39), in the present study, we found that maintaining an ideal weight, being healthy, and inducing a variation in the diet are all among the significant benefits of FV consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive and behavioral activities promoting the level of self-efficacy and optimism, and increasing the level of satisfaction with life can be useful in the improvement of nutrition in various population groups [34], including menopausal women. Previous studies revealed that reliable education programs promote internal locus of control and self-efficacy of women [35].…”
Section: H -High M -Moderate or L -Low Level Of Self-efficacy (Gsesmentioning
confidence: 99%
“…According to Tung et al, 21 to alter the conception about the conditions of discouragement to the desired behavior can result in the effects of long duration of this behavior. After an extensive literature review, there has been no studies investigating the effect of the interventions based on the Decisional Balance in relation to breastfeeding, however Salehi et al 22 demonstrated a reduction in the conception of the discouraging conditions by increasing the consumption of fruit and vegetables for elderly Iranians. The Decisional Balance construct assessment contributed to the knowledge of the interfering factors in the decision making process of breastfeeding in the studied group.…”
Section: Discussionmentioning
confidence: 99%